2007
DOI: 10.1080/17453670710013672
|View full text |Cite
|
Sign up to set email alerts
|

Continuous psoas and sciatic block after knee arthroplasty: good effects compared to epidural analgesia or i.v. opioid analgesia: A prospective study of 63 patients

Abstract: Introduction For endoprosthetic knee surgery, intensive postoperative pain therapy is necessary. We therefore evaluated whether the combination of continuous psoas compartment and sciatic analgesia (PSC) is as effective as epidural analgesia (EPI) and whether it provides better analgesia than patient-controlled intravenous analgesia with piritramide (PCA).Methods We studied 63 patients who underwent total knee arthroplasty (TKA). The PSC group received a combination of continuous psoas and sciatic nerve block,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Raimer et al recorded that patient satisfaction with the anesthetic technique was high, and no significant differences were observed between psoas compartment-sciatic analgesia and epidural analgesia for postoperative pain therapy after knee arthroplasty 19. We investigated satisfaction of both the patients and the surgeons.…”
Section: Discussionmentioning
confidence: 95%
“…Raimer et al recorded that patient satisfaction with the anesthetic technique was high, and no significant differences were observed between psoas compartment-sciatic analgesia and epidural analgesia for postoperative pain therapy after knee arthroplasty 19. We investigated satisfaction of both the patients and the surgeons.…”
Section: Discussionmentioning
confidence: 95%
“…Contrary, Raimer et al described better analgesia with continuous psoas and sciatic blocks or epidural catheters compared to opioid PCA regarding pain levels, analgesic requirements, and patient satisfaction. However, there was no difference in functional outcome between the 3 groups [229]. …”
Section: Functional Outcomementioning
confidence: 99%
“…On the other hand, performing a post-TKA continuous PCB together with a sciatic nerve block has been reported to be as effective as a continuous epidural nerve block for pain control [18]. The presented study would have had better results if a sciatic nerve block was performed as well.…”
Section: Discussionmentioning
confidence: 83%
“…Watson et al [19] and Raimer et al [18] reported that continuous PCB also resulted in lower pain scores and fewer incidences of side effects such as nausea and sedation when compared to IVPCA. In the present study, the postoperative pain scores 6 hours after surgery between Group IVPCA and Group PCB were not very different.…”
Section: Discussionmentioning
confidence: 99%